An azo dye for photodynamic therapy that is activated selectively by two-photon excitation - Juvekar, Vinayak; Lim, Chang Su; Lee, Dong Joon; Park, Sang Jun; Song, Gyeong Ok; Kang, Hyuk; Kim, Hwan Myung (Chemical Science, 2021)
Two-photon photodynamic therapy (TP-PDT) is a promising approach for the treatment of cancer because of its better penetration depth and superior spatial selectivity. Here, we describe an azo group containing cyclized-cyanine derivatives (ACC1 and ACC2) as a two-photon activated, type I based photosensitizer (PS). These small-molecule and heavy atom-free organic dyes showed marked reactive oxygen species (ROS)-generating ability under physiological conditions, as well as fast loading ability into the cells and negligible dark toxicity. Live cell analyses with one- and two-photon microscopy revealed that these dyes showed higher ROS generation ability upon two-photon excitation than upon one-photon excitation via the type I process. The PSs have superior PDT properties compared to conventional Visudyne and 5-ALA under mild conditions. These characteristics allowed for precise PDT at the target region in mimic tumor spheroids, demonstrating that the developed TP PS could be useful in efficient PDT applications and in designing various PSs.
Keywords: One photon excitations; Physiological condition; Ros generations; Small molecules; Spatial selectivity; Two photon microscopy; Two-photon excitations; Two-photon photodynamic therapies